EFFECTIVENESS OF PEER GROUP SUPPORT IN THE APPLICATION OF ACUPRESSURE AND ABDOMINAL STRETCHING ON MENSTRUAL PAIN IN ADOLESCENT FEMALES WITH THE SELF DETERMINATION MODEL - Rosari Oktaviana Mahundingan; Dewi Andriani; Dwi Yuniar Ramadhani (Nurse and Health)
Background: One of the changes that appears in adolescent is menstruation. One way to reduce menstrual pain is to use relaxation techniques, acupressure, and abdominal stretching. Another way is to help teenagers deal with pain by using group methods, such as peer group support.